2000
DOI: 10.4049/jimmunol.164.2.558
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: Heat Shock Protein 60 Is a Putative Endogenous Ligand of the Toll-Like Receptor-4 Complex

Abstract: Human heat shock protein 60 (hsp60) elicits a potent proinflammatory response in cells of the innate immune system and therefore has been proposed as a danger signal of stressed or damaged cells. We report here that macrophages of C3H/HeJ mice, carrying a mutant Toll-like-receptor (Tlr) 4 are nonresponsive to hsp60. Both the induction of TNF-α and NO formation were found dependent on a functional Tlr4 whereas stimulation of macrophages by CpG DNA was Tlr4 independent. We conclude that Tlr4 mediates hsp60 signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
937
6
20

Year Published

2001
2001
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,467 publications
(990 citation statements)
references
References 32 publications
20
937
6
20
Order By: Relevance
“…These include HMGB1 76 31, uric acid 77 , some HSPs 78 79, some defensins [G] 80 , hyaluronic acid 81 , heparan sulfate 82 , and some fragments of extracellular matrix proteins 70 . Whereas this data may well be correct, caution is warranted because TLRs can be stimulated by microbial contaminants that are easily introduced during the purification of molecules.…”
Section: Receptors For Dampsmentioning
confidence: 99%
“…These include HMGB1 76 31, uric acid 77 , some HSPs 78 79, some defensins [G] 80 , hyaluronic acid 81 , heparan sulfate 82 , and some fragments of extracellular matrix proteins 70 . Whereas this data may well be correct, caution is warranted because TLRs can be stimulated by microbial contaminants that are easily introduced during the purification of molecules.…”
Section: Receptors For Dampsmentioning
confidence: 99%
“…Interestingly, tissue damage in response to ischaemia-reperfusion also requires intact TRL4, again indicating that endogenous TLR4 ligands are produced during local stress [98]. We have previously identified heat shock protein 60 as one such 'danger antigen' [99].…”
Section: Synthesis and Open Questions/suggestions For Studiesmentioning
confidence: 99%
“…Recognition of endogenous ligands by TLRs is also an area of active investigation due to its potential relevance to autoimmune diseases, noninfectious inflammatory disorders, and elimination of neoplastic or damaged cells. A number of putative endogenous TLR ligands have already been studied in vitro, including heat shock protein 60 (Hsp60), 78 fibronectin, 79 and the extra domain A of fibrinogen. 80 Recent data have also demonstrated that low-molecular weight soluble hyaluronan (sHA) fragments derived from the extracellular matrix at sites of inflammation are able to induce DC maturation in vitro as well as in vivo through TLR4.…”
Section: Future Directionsmentioning
confidence: 99%